A Novel Glucose Sensor Using Lutetium Phthalocyanine as Redox Mediator in Reduced Graphene Oxide Conducting Polymer Multifunctional Hydrogel. (2017) - Al-Sagur, H.; Komathi, S.; Khan, A.; Gurek, A.G.; Hassan, A.
Abstract: Herein, we report a scalable synthesis of multifunctional conducting polyacrylic acid (PAA) hydrogel (MFH) integrated with reduced grapheme oxide (rGO), vinyl substituted polyaniline (VS-PANI) and lutetium phthalocyanine (LuPc2 ) as three dimensional robust matrix for glucose oxidase (GOx) immobilization (PAA-rGO/VS-PANI/LuPc2 /GOx-MFH). We have integrated the multicomponents such as PAA with rGO, VS-PANI through free radical polymerization using methylene bis-acrylamide, ammonium persulphate as the cross linker and initiator. The LuPc2 was then doped to form multifunctional hydrogel (PAA-rGO/VS-PANI/LuPc2 -MFH). Finally, biosensor was fabricated by immobilizing GOx into PAA-rGO/VS-PANI/LuPc2 -MFH and subsequently used for electrochemical detection of glucose.